Herbage Yield and Quality of Two Vegetative Parts of Indigofera at Different Times of First Regrowth Defoliation - L Abdullah; . Suharlina (Media Peternakan, 2010)
A field experiment using Indigofera sp. was conducted at the Farm Research Station of Faculty of Animal Science, Bogor Agricultural University, Darmaga Campus, during 2008-2009. The objectives of this study were to identify the effect of defoliation time on herbage dry-matter production, protein, fiber contents, and in vitro digestibility of different vegetative parts of Indigofera sp.  Block randomized design comprising three levels of defoliation time at first regrowth after pruning (38, 68, and 88 days) with 3 replications were used in this experiment. Pruning was done 3 months after transplanted into the experimental plots. First defoliation was conducted after the plant had been pruned. Herbage was derived from different vegetative parts, i.e: leaves of branch base and all parts of shoot tips. The results revealed significant effect of defoliation time on dry matter (DM) production of both branch base and shoot tip herbages. Crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF) and in vitro organic matter digestibility (IVOMD) of branch base were influenced significantly by defoliation time, except crude protein (CP) and in vitro dry matter digestibility (IVDMD). Defoliation time significantly affected CP, CF, NDF, ADF, IVDMD and IVOMD of herbage derived from shoot tips.   Key words: Indigofera, defoliation time, herbage quality, herbage yield